2015
DOI: 10.1371/journal.pgen.1005681
|View full text |Cite
|
Sign up to set email alerts
|

Convergent Evolution of Hemoglobin Function in High-Altitude Andean Waterfowl Involves Limited Parallelism at the Molecular Sequence Level

Abstract: A fundamental question in evolutionary genetics concerns the extent to which adaptive phenotypic convergence is attributable to convergent or parallel changes at the molecular sequence level. Here we report a comparative analysis of hemoglobin (Hb) function in eight phylogenetically replicated pairs of high- and low-altitude waterfowl taxa to test for convergence in the oxygenation properties of Hb, and to assess the extent to which convergence in biochemical phenotype is attributable to repeated amino acid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
172
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 113 publications
(193 citation statements)
references
References 88 publications
15
172
3
1
Order By: Relevance
“…It is possible that hypoxia exposure associated with breath-holding diving led to exaptations ( pre-adaptations) for life at high altitudes in lowland torrent ducks, and reduced the selective advantage for adaptive changes in some traits in the high-altitude population. Consistent with this idea, both high-and low-altitude populations of torrent ducks have hemoglobin with an affinity (P 50 =33-35 mmHg) that is much greater than most birds (in which P 50 typically ranges between 44 and 52 mmHg) and is comparable to that of the emperor penguin (P 50 =28-36 mmHg) (Christensen and Dill, 1935;Hirsowitz et al, 1977;Lutz, 1980;Wastl and Leiner, 1931;Meir and Ponganis, 2009;Tamburrini et al, 1994;Natarajan et al, 2015). However, unlike highland populations of many other South American waterfowl, highland torrent ducks lack further evolved specialization in hemoglobin sequence or O 2 -binding affinity compared to their lowland counterparts (McCracken et al, 2009a,b).…”
Section: Potential Importance Of Evolved Trait Differences Versus Plamentioning
confidence: 90%
See 2 more Smart Citations
“…It is possible that hypoxia exposure associated with breath-holding diving led to exaptations ( pre-adaptations) for life at high altitudes in lowland torrent ducks, and reduced the selective advantage for adaptive changes in some traits in the high-altitude population. Consistent with this idea, both high-and low-altitude populations of torrent ducks have hemoglobin with an affinity (P 50 =33-35 mmHg) that is much greater than most birds (in which P 50 typically ranges between 44 and 52 mmHg) and is comparable to that of the emperor penguin (P 50 =28-36 mmHg) (Christensen and Dill, 1935;Hirsowitz et al, 1977;Lutz, 1980;Wastl and Leiner, 1931;Meir and Ponganis, 2009;Tamburrini et al, 1994;Natarajan et al, 2015). However, unlike highland populations of many other South American waterfowl, highland torrent ducks lack further evolved specialization in hemoglobin sequence or O 2 -binding affinity compared to their lowland counterparts (McCracken et al, 2009a,b).…”
Section: Potential Importance Of Evolved Trait Differences Versus Plamentioning
confidence: 90%
“…However, there is very little genetic variation across altitudinal gradients in torrent ducks and gene flow between high and low altitudes is likely significant (McCracken et al, 2009a,b;Natarajan et al, 2015;K.G.M., unpublished). Therefore, if the observed differences in muscle physiology in highland torrent ducks arose as evolutionary adaptations to the high-altitude environment, then these differences are presumably under very strong selection.…”
Section: Potential Importance Of Evolved Trait Differences Versus Plamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, RADseq is very useful for studies of local adaptation where candidate genes have already been identified because RAD markers can be used to generate a null distribution of loci across the genome (Luikart et al 2003). Natarajan et al (2015) recently conducted an excellent study of this sort with candidate alpha-and betaglobin genes in ducks. They compared allele frequencies of these candidate genes to a null distribution generated by RADseq data for high-and low-altitude population pairs of three Andean duck species.…”
Section: If You Radmentioning
confidence: 99%
“…For example, birds typically express two main Hb isoforms in definitive red blood cells -a major isoform, HbA, which incorporates α-type products of the α A -globin gene, and a minor isoform, HbD, which incorporates α-type products of the α D -globin gene; the two isoforms share the same β-type subunits Grispo et al, 2012;Opazo et al, 2015). In all bird species that have been examined to date, the minor HbD isoform has an appreciably higher O 2 affinity than the major HbA isoform in the presence of allosteric effectors (Grispo et al, 2012;Projecto-Garcia et al, 2013;Cheviron et al, 2014;Galen et al, 2015;Natarajan et al, 2015bNatarajan et al, , 2016. Other sauropsid taxa also tend to co-express multiple, structurally distinct Hb isoforms in definitive erythrocytes (Weber and Jensen, 1988;Storz et al, 2011bStorz et al, , 2015bDamsgaard et al, 2013).…”
Section: Heterotropic Allosterymentioning
confidence: 99%